Architect’s visual alphabet: the initiation to the exercise of projecting: Investigación para la innovación docente en la iniciación al ejercicio de proyectar - Millán-Millán, Pablo Manuel; Candel-Rubio, Ignacio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The development of an architect always travels between two worlds, the virtual (image, technique) and the real (practice, construction). Starting from this dichotomy, there is a common element to both worldviews: the visual alphabet necessary in the architect's training. This article summarizes the research carried out as part of the "Projects I" course of the Degree in Architecture in the Department of Architectural Projects. The objectives set out in it have sought to answer the questions of what is the "architect's alphabet" and what are the tools needed to understand the "architect's language".